Management of floral waste generated from temples of Jaipur city through vermicomposting - Tiwari, Priyanka; Juneja, Shelja K (International Journal of Environment, 2016)
This paper aims at management of floral waste generated from temples of Jaipur city through vermicomposting. In this study, flower waste consisted of variety of flowers out of which marigold was chosen as it was found in maximum amount. The vermibeds were prepared by mixing the marigold with cow dung in different proportions viz., 50:50, 60:40, 70:30, 80:20 and 90:10 and they were filled in the earthen pots, individually. Simultaneously, a control (without worms) for each of these concentrations was prepared and maintained. Eisenia foetida was introduced into each of these trays except the control. The bioconversion ratio i.e., waste into vermicompost was found to be high in 60:40 proportion than the others. Vermicompost obtained was analysed for various parameters like organic carbon, total nitrogen, phosphorus, potassium, calcium and magnesium. The amount of organic carbon, potassium and phosphorus was more in vermicompost samples for all the groups as compared to compost samples. It was concluded that floral waste with cow dung at 50:50, 60:40 and 70:30 ratios could be converted into a nutrient rich vermicompost. International Journal of Environment Vol. 5 (1) 2016, pp: 1-13